FERTILITY IN WOMEN AFTER LAPAROSCOPIC SALPINGOSTOMY WITH EVACUATION OF THE EMBRYO IN THE TREATMENT OF ECTOPIC TUBAL PREGNANCY - Лариса Егоровна Фетищева (Мать и дитя в Кузбассе, 2019)
The aim of the research – to study fertility in women after laparoscopic salpingostomy with the evacuation of the embryo in the treatment of ectopic pregnancy.